Myeloma coexisting with jejunal light chain amyloidosis - Marimuthu, Aishwarya K.; Ramkumar, Purnima; Abdulsalam, Mohammed S.; Pandurangan, Prabu; Jameel, Jainudeen Khalander Abdul; Menon, Maya (International Journal of Research in Medical Sciences, 2020)
Amyloid Light chain (AL) amyloidosis is a rare disease, which is seen in approximately one-tenth of patients with multiple myeloma. We report a 52 years old male, who presented with complaints of anorexia and weight loss. He was diagnosed to have multiple myeloma-international staging score (ISS) Stage 3 and was started on VTD (Bortezomib, Thalidomide, and Dexamethasone) chemotherapy. Within 2 weeks of therapy, he had abdominal symptoms like abdominal pain, loose stools, vomiting and hematochezia. Imaging showed dilated proximal bowel loops with fluid filled contents and prominent vessels in rectum. Emergency surgical exploration revealed thickened proximal jejunum with blood clots in the lumen. Resection of proximal jejunum was done. Histopathological examination of resected specimen was suggestive of AL amyloidosis. Post-surgical resection of jejunum, patient had initial improvement followed by deterioration. He was discharged against medical advice as per relative’s request. Hence an index of clinical suspicion of amyloidosis must been present in all Multiple myeloma patients.